Annual Report on Exchange Arrangements and Exchange Restrictions 1982. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1982)
Annual Report on Exchange Arrangements and Exchange Restrictions 1982.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet